The Position and Participation of Khadijah in Developing Da'wah in Islam at the First Period - Saiful Bahri; Maria Ulfa Batoebara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Women are always interesting issues to be made into a study, both in countries that are Muslim majority and non-Muslim majority. Admittedly or not, the presence of women on this earth has a very important role. They are a part of this life, however, it is still felt by at least people who are aware of this. Many women have succeeded in carrying out their role, so it is worthy of being a good role model and teaching especially for Muslims in particular. One of the women who needed to be a role model was Khadijah as the first wife of the Prophet. Khadijah is a phenomenal figure, integrity, self-purity, faith, and her commitment to continue to support and sacrifice for the success of the Prophet's preaching. Moving on from that thought, the authors can explain that Khadijah was already well known among the Muslims only limited to the wife of the Prophet Muhammad, but the position and participation of Khadijah in developing Islam in the first period were less noticed by the Eve today. Whereas the most important thing that needs to be understood from Khadijah is the position and participation of Khadijah to be a good role model for women today. Furthermore, the authors can conclude from this paper that Khadijah always participated in the struggle of the Prophet, since before becoming the wife of the Prophet and after becoming her husband. In general there are three things that motivate Khadijah in the struggle of the Prophet, namely the personality of the Prophet, Khadijah's love for the Prophet and Khadijah's belief in the truth of Islamic teachings. Khadijah's sacrifice in developing Islam which is greatest was her body and soul.